Electromagnetic Optimization of the Coils of Magnetic Coupling Resonant Wireless Energy Transmission System - Xingwei Zhu (Chemical Engineering Transactions, 2018)
To develop and study the electromagnetic optimization of the coils of magnetic coupling resonant wireless energy transmission system. Compared with the traditional technology, this paper adopts magnetic coupling resonant WPT technology to optimize the traditional technology. In this paper, the finite-element analysis software Maxwell is used to perform the electromagnetic simulation analysis of the coupling coils and then the comparison and research are conducted on the traditional specification to confirm whether the design can achieve the goal. The results of the analysis show that the designed magnetic leakage flux is reduced within the safety limit and achieve the optimization goal.